PE_PGRS3 ensures provision of the vital phospholipids cardiolipin and phosphatidylinositols by promoting the interaction between M. tuberculosis and host cells - De Maio, Flavio (Virulence, 2021)
PE_PGRS proteins of Mycobacterium tuberculosis (Mtb) constitute a large family of complex modular proteins whose role is still unclear. Among those, we have previously shown, using the heterologous expression in Mycobacterium smegmatis, that PE_PGRS3 containing a unique arginine-rich C-terminal domain, promotes adhesion to host cells. In this study, we investigate the role of PE_PGRS3 and its C-terminal domain directly in Mtb using functional deletion mutants. The results obtained here show that PE_PGRS3 is localized on the mycobacterial cell wall and its arginine-rich C-terminal region protrudes from the mycobacterial membrane and mediates Mtb entry into epithelial cells. Most importantly, this positively charged helical domain specifically binds phosphorylated phosphatidylinositols and cardiolipin, whereas it is unable to bind other phospholipids. Interestingly, administration of cardiolipin and phosphatidylinositol but no other phospholipids was able to turn-off expression of pe_pgrs3 activated by phosphate starvation conditions. These findings suggest that PE_PGRS3 has the key role to serve as a bridge between mycobacteria and host cells by interacting with specific host phospholipids and extracting them from host cells, for their direct integration or as a source of phosphate, during phases of TB pathogenesis when Mtb is short of phosphate supply.